Review of the evidence on the rate of return to employers of investment in training and employer training measures - Keep, E; Mayhew, K; Corney, M (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2002)
This report was commissioned to review the existing evidence on the returns to employer investment in training. What follows provides probably the most detailed and comprehensive, and certainly the most up to date, overview of the research base in this area.